Jurnalisme Lingkungan pada Foto Berita di Media Online - Dwi Ratmono; Rohmadtika Dita (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This study examines environmental journalism in news photos in the online media Antarafoto.com. The ecological issue studied is the protection of wild animals, namely the Sumatran tiger in Aceh Province. The focus of the study is on environmental journalism, namely chronic points that provide information about the condition of the Sumatran tiger. Points of criticism and comments, namely a vehicle for education, raising awareness and providing solutions for the government and society. The research method used is Roland Barthes’ semiotics. The results of the analysis of news photos, namely denotations, describe the condition of the Sumatran tiger in the process of evacuating, caring for, and releasing it to its natural habitat. Connotation, showing six procedures: trick effect, pose, object, photogenic, aestheticism, and syntax. The selection of compositions, objects, and photo captions is essential to highlight in news photos so that they are easy to understand. The myth emphasizes the importance of the process of protecting the Sumatran tiger in Aceh. Antarafoto.com showcases environmental journalism by providing information on dealing with the problem of Sumatran tiger poaching. They appear in a news photo showing the Sumatran tiger evacuation process by Aceh Natural Resources Conservation Center (BKSDA) officers, the treatment process at the Conservation Response Unit in Naca Village, Trumon, Aceh, and the release process in the Leuser Ecosystem Area, Gayo Lues Regency, Aceh. Antarafoto.com has not presented environmental journalism that can provide solutions for the government and society in realizing the critical role of managing the environment in dealing with the endangered Sumatran tiger